Bluetooth Low Energy based inertial sensors test and verification tool - Amaro, J. Pedro; Patrao, Sergio (IECON 2016 - 42nd Annual Conference of the IEEE Industrial Electronics Society, 2016)
The development of Micro-Electro-Mechanical Systems based inertial sensors is the basis of an increasing number of commercial and scientific solutions for unmanned vehicles aeronautical/aerospace navigation systems and health and sports monitoring solutions. Inertial sensors widespread use within embedded systems also prompted the development of algorithms to cope with their inherent inaccuracy. These sensors, with small form factor and low cost, present an advantage for computing three-dimensional space object orientation. Also radio frequency communication devices are frequently associated with inertial sensors and embedded systems. Radio frequency communication protocols allow immediate data transfer and processing without cumbersome cabling. This work proposes a Bluetooth Low Energy based framework to evaluate the behavior of inertial sensors fusion algorithms. A Yaskawa Motoman NX100 robotic arm has been used to implement a set of predefined movements that granted the mandatory test accuracy and repeatability conditions. The Bluetooth Low Energy device has been implemented to transfer the inertial sensor data to a PC computer running a Windows operating system. The inertial sensors have been implemented with a MPU-9150 Inertial Measurement Unit (IMU) that includes an accelerometer, a gyroscope and a compass. The proposed framework has been used to test and verification of a number of sensor fusion algorithms.